Evaluating the effectiveness of surgical detoxification treatment of inflammatory and vascular eye diseases - L. P. Danilova; V. V. Egorov; G. P. Smoljakova; L. P. Emanova; D. A. Povaljaeva (Oftalʹmologiâ)
Purpose: to study the advantages and the efficiency of improvement of the surgical detoxification in patients with inflammatory and vascular eye diseases.Patients and Methods. Examination included visometry with maximum correction, optical coherence tomography (OCT), ophthalmoscopy, fluorescein angiography (FAG), B-scan.Results. The study was performed in 53 eyes of 53 patients (age from 45 to 60 years). There were 21 men, 32 women. 19 observed patients (19 eyes) had a partial or subtotal hemophthalmus. 34 patients (34 eyes) were observed for chronic recurrent uveitis. A significant decrease of blood in the vitreous was showed after treatment in 19 patients with hemophthalmus according to B-scan. Complete resorption of hemophthalmus and improvement in visual acuity (average: 0.71±0.15) was noted in 76,6%. In 14 from 34 people with chronic recurrent uveitis macular edema occurred. 3 months after surgical treatment retinal thickness in macular area decreased to an average of 256.3±9.2 mm. At the same time, there was an increase in visual acuity to an average of 0.65±0.05. Among 15 patients (15 eyes) with inflammatory exudation in the vitreous body against recurrent chronic uveitis there was a complete relief of symptoms of inflammation in 7‑10 days after surgical treatment in 78.4% of patients. In the remaining 26.6% the inflammatory exudates resorption in the vitreous occurred by 12‑15 day after the operation.Conclusion. The proposed method of ophthalmodetoxification is a promising method of treatment of chronic recurrent uveitis and vascular eye diseases. Terms of recovery of patients with inflammatory and vascular eye diseases were reduced by 30% and visual acuity achieved at discharge exceeded 3.2 times the original level.